CHARACTERISTIC OF RATS AS RESERVOIRS OF LEPTOSPIROSIS IN BEJI VILLAGE DISTRICT OF KEDUNG BANTENG AND KEDUNG PRING VILLAGE DISTRICT OF KEMRANJEN BANYUMAS CENTRAL JAVA - Marbawati, Dewi (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2016)
Background: World Health Organization (WHO) estimates that the incidence of leptospirosis was â¥ 500.000 cases annually with worldwide distribution. The Case Fatality Rate (CFR) of leptospirosis in Indonesia in 2004-2012 reached > 5%. Leptospirosis in Banyumas discovered since 2010 and until May 2014 found two suspected leptospirosis in Beji Village District of Kedung Banteng and Kedung Pring village District of Kemranjen. The purpose of this study was to identify the reservoir of leptospirosis. Method: The study was cross-sectional. The Location conducted in Kedung Pring village, Kemranjen sub district and Beji village, Kedung Banteng sub district in Banyumas. Result: The species that found in the location were Rattus tanezumi and Suncus murinus, but in Beji village also founded the Mus musculus. The trap success in each location was 15% for Beji Village kedung Banteng sub district and 14.14% for Kedung Pring village, Kemranjen sub district. Concusion: All of species that found in the study are known potentially to transmit leptospirosis.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Keywords: Leptospirosis, Banyumas, Rats